2006
DOI: 10.1364/josab.23.000318
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of optical parametric amplification cross-correlation frequency-resolved optical gating

Abstract: We perform numerical simulations of cross-correlation frequency-resolved optical gating with the nonlinearities, optical parametric amplification, and difference-frequency generation for measuring broadband pulses. We show that use of a noncollinear beam geometry that matches the group velocities of the pump, signal, and idler pulses permits use of relatively thick crystals for high gain without significant distortion in the measured trace, yielding bandwidths of ϳ100 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The time-frequency distribution provided by the cross-correlation frequency-resolved optical gating (XFROG) technique provides a particularly useful representation for the complex temporal and spectral evolution associated with WLC generation. For instance, in previous experiments the XFROG technique was successfully used for characterizing the continuum generation in photonic-crystal fibres or microstructure fibres [23,24], and the continuum generated by 800 nm pulses in bulk media such as CaF 2 , sapphire and fused silica was measured by using the related techniques of difference frequency generation XFROG and optical parametric amplification XFROG [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The time-frequency distribution provided by the cross-correlation frequency-resolved optical gating (XFROG) technique provides a particularly useful representation for the complex temporal and spectral evolution associated with WLC generation. For instance, in previous experiments the XFROG technique was successfully used for characterizing the continuum generation in photonic-crystal fibres or microstructure fibres [23,24], and the continuum generated by 800 nm pulses in bulk media such as CaF 2 , sapphire and fused silica was measured by using the related techniques of difference frequency generation XFROG and optical parametric amplification XFROG [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al [10] used the shorter length PCF in XFROG setup with crystal dithering to characterize the continuum generated in the propagation regime of the fiber and supercontinuum generation was characterized by employing XFROG, which was generated from PCF [11]. Zhang and Liu et al [12][13][14] employed complex techniques like optical parametric amplification XFROG (OPA-XFROG) and difference frequency XFROG (DF-XFROG). Lee et al [15] reported an alternative approach of single-short measurement of continuum pulses using transient grating XFROG (TG-XFROG) a third-order nonlinear medium, but in practice they were limited to acquiring five to six shots.…”
Section: Introductionmentioning
confidence: 99%